Relationship among stress, depression, cardiovascular and metabolic changes and physical exercise - Andrea Sanches; Rafaela Costa; Fernanda Klein Marcondes; Tatiana Sousa Cunha (Fisioterapia em Movimento)
Abstract Introduction: Stress is considered one of the most significant health problems in modern society. It can be characterized as any changes in the homeostasis of an individual that require an adaptive response. An imbalance in the secretion of the primary stress mediators may be responsible for the onset and development of several diseases. Thus, chronic stress has been recognized as a risk factor for depression as well as cardiovascular and metabolic diseases. Given the pathophysiological mechanisms associated with chronic stress and related cardiovascular and metabolic changes, it is necessary to implement measures to prevent, control and/or avoid their development. Physical exercise is a non-pharmacological resource that is widely used for this purpose. Its beneficial effects include the improvement of the emotional state as well as lipid and glycemic control. Objective: The aim of this review is to discuss the relationship between stress, depression, cardiovascular and metabolic changes, and highlight the importance of physical exercise in the prevention and treatment of resulting disorders. Materials and Methods: We searched MEDLINE and SCIELO from 2000 through 2012, using the terms chronic stress, mood disorders, depression, cardiovascular and metabolic changes, and exercise. Results: Most of the studies found in our literature search have shown that exercise can attenuate and/or reverse the deleterious effects of chronic stress. Conclusion: Regular physical exercise is useful for maintaining health, especially with respect to improving mood and mental stress.